KEBIJAKAN ORGANISASI KERJASAMA ISLAM MEMBEKUKAN STATUS KEANGGOTAAN SURIAH - Ade Ruhanda; Syafri Harto (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
This research describes the policy of the organization of Islamic conference revokemembership status in Syria. Organization of Islamic Conference is a non-militaryorganization founded in rebates, Morocco on 25 September 1969, Syria is one of the memberstates of the organization of Islamic conference. conflict in Syria is a complex problem whichis a violation of human rights, the number of casualties and the absence of securityguarantees for the citizens.The research method used is descriptive qualitative research method of the facts. Thisstudy is an explanation that describes the problem, indications, policies, and actions. Intechnical writing, the authors collected and compiled the data through the study of literaturefrom multiple sources such as books, journals, articles, websites, and other media. Theauthor also uses the concept to International organizations and the concept of internationalcooperation.This research demonstrates a policy taken by the organization of Islamic conferenceon political conflict in Syria. in addition, the conflict has become a political discussion ofmost of the other members of the Organization of Islamic Conference. long span of time insyria conflict settlement solution without causing the organization of Islamic conference syriarevoke membership status in 2012 based on the results of ministerial meetings and summitsremarkable Organization of Islamic Conference which was held in Makkah Al-Mukaramah14th in Saudi Arabia -15 August 2012.Keywords: Policy, Conflict, Organization of Islamic Conference, Syria